Motion compensated spin echo cardiac diffusion tensor imaging in multiple cardiac phases using an ultrahigh gradient strength scanner - Paul,S; Munoz,C; Ferreira,P; Evans,CJ; Foley,S; Fasano,F; Jones,D; Pennell,D; Nielles-Vallespin,S; Scott,A (Journal of Cardiovascular Magnetic Resonance, 2026)
BackgroundCardiac diffusion tensor imaging (cDTI) has traditionally relied on inefficient stimulated echo techniques to robustly assess microstructural changes over the cardiac cycle. Ultrahigh gradient strength systems (>80mT/m) allow shorter motion compensated diffusion encoding. This study compares the ability of high and ultrahigh strength gradient systems to provide systolic and diastolic motion compensated spin echo (MCSE) cDTI.MethodsSecond order MCSE sequences were developed for a research-only Siemens 3T Connectom (300mT/m maximum gradient amplitude per axis) and breath hold cDTI was acquired at peak systole and end diastole. Acquisitions used the maximum achievable gradient strength (GUH, 116mT/m) and also limited to typical high gradient strengths (GH, 66mT/m based on 80mT/m maximum allowable), giving TE=48ms and 58ms respectively. Data were acquired at 2.8x2.8x8mm3, b=500s/mm2 (8 averages) and b=150s/mm2 (2 averages) in 6 encoding directions.Results22 healthy subjects were recruited. 20/21 and 21/22 systolic acquisitions at GUH and GH respectively met the >50% criteria of the circumferential myocardium showing the expected transmural variation in helix angle. For GUH and GH (16/20) 80% and (16/22) 73% of diastolic acquisitions were successful respectively. SNR was increased using GUH compared to GH (median [IQR]: 112.9 [3.8] vs. 9.6 [2.9], p=0.0002 diastole, 15.6 [5.9] vs. 12.5 [6.7], p=0.006 systole). Using GUH fractional anisotropy was lower in systole (0.349 [0.040] vs. 0.373 [0.019], p=0.002) and GUH transmural helix angle gradient (HAG) was steeper in diastole (-0.70 [0.17] vs. -0.55 [0.12] /%, p=0.04). At both GUH and GH, sheetlet angle (|E2A|) was higher in systole than in diastole (30.7 [7.3] vs. 21.3 [6.7] p=10-4 and 32.6 [10.9] vs. 26.0 [7.4], p=0.03 respectively). Differences in HAG between phases were only apparent with GH (-0.88 [0.23] vs. -0.55 [0.15], p=10-4) and differences in the mean diffusivity only with GUH (1.64 [0.11] vs